Model Pendidikan Bagi Anak Abk; Sekolah Inklusi, Sekolah Abk, Dan Home Schooling - Fiddini Izaturahmi; Indah Ramadhany; Winda Sugiarti; Muhammad Alif Al Aziz; Wismanto Wismanto (LPPM Politeknik Pratama, 2024)
Generally, there are three education options for children with special needs (ABK): Special Schools (SLB), Inclusive Schools, and Home Schooling. Every child has the right to education and the right to choose an educational style that suits their interests, talents, abilities, and learning styles, including Children with Special Needs. When facing challenges in SLB or Inclusion, parents tend to choose Home Schooling as an alternative. This research aims to explore the education model for ABK through Home Schooling. The research method used is library research, with data analysis techniques in the form of content analysis. The research findings indicate that Home Schooling is an alternative education option that can be chosen by the community. The homeschooling approach is more flexible compared to the formal school environment. Home Schooling is considered an alternative step to achieving national education goals, which are to develop the potential of learners and improve the intelligence of the nation.